Masculinization, growth and survival of tilapia Oreochromis niloticus using natural and synthetic aromatase inhibitors: Tilapia masculinization using flavonoids - Estrada-Godínez, José Antonio; Alaníz-González , Anabel; Abdo-de la Parra, María Isabel; Bañuelos-Vargas, María Isaura; Rodriguez-Montes de Oca, Gustavo Alejandro (Ecosistemas y Recursos Agropecuarios, 2024)
The effect of natural and synthetic aromatase enzyme inhibitors on growth, survival, and masculinization in Nile tilapia offspring was evaluated. Five flavonoids: chrysin (CRI), 7-hydroxyflavone (7-HF), apigenin (NA), naringenin (NAR), and 7-methoxyflavone (7-MF) at 1 000, 1 500, and 2 000 mg kg-1; a non-steroidal compound: letrozole (LT) at 50, 100, and 200 mg kg-1; and two synthetic steroids: exemestane (EXE) at 1 000, 1 500, and 2 000 mg kg-1, and 17 α-methyltestosterone (MT) at 60 mg kg-1 (C+), with a negative control free of compounds (C-). Each treatment was conducted in triplicate with n = 30 fish per replicate (0.012 ± 0.01 g) in cylindrical tanks (6 L) with continuous flow at 28°C. The 7-HF groups at 1 000 and 2 000 mg kg-1 showed significantly higher specific growth (16.08 ± 0.63% and 8.38 ± 2.11%, respectively). Survival was 100%, except for 7-HF 2,000 mg kg-1, NA 1,500 mg kg-1, 7-MF at 1 500 mg kg-1, and EXE at 1 500 and 2 000 mg kg-1, with 80 and 90%. The percentage of males in MT, EXE, and LT was 100%, but the flavonoid treatments varied, increasing from 57% males in C- to 71 to 86% for CRI 2 000, 7-HI 1 500, and all inclusion levels of 7-MET, NA, and NAR treatments. Further evaluation is expected to establish the concentration of natural inhibitors closer to 100% males.